Knowledge and ability of early childhood teachers in delivering career guidance for preschooler - Anesty, Esya; Fatihaturrosyidah, Fatihaturrosyidah; Putra, Jeni (ProGCouns: Journal of Professionals in Guidance and Counseling, 2022)
The level of knowledge and ability of teachers in delivering career guidance is very influential on the child's self-development process, especially in the aspects of career orientation and career attainment. In this regard, this study aims to identify the knowledge and ability of early childhood education teachers in delivering career guidance for preschoolers. By using a descriptive method, data were collected using observation techniques and a self-report questionnaire, from 12 early childhood teachers in Serang City, Banten, Indonesia. The results showed that the level of knowledge and ability of early childhood education teachers in delivering career guidance services may be described in five areas: (1) needs assessment: analyzing student needs for guidance and counseling services; (2) program development: preparing the guidance and counseling service programs; (3) selecting methods/techniques/strategies: creating the most prospective guidance and counseling methods/techniques/strategies and conducting step by step of guidance activities based on selected method; (4)  content development: designing guidance and counseling materials; and (5) accountability: evaluating the guidance and counseling service activities. Howeverm the adequate level of knowledge and ability at expert level was not found in any of these areas, adequate level of knowledge and ability at moderate level was found in areas (3) and (4), while inadequate level of knowledge and ability at novice level was in areas (1), (2), and (5). As a consequence, policy makers, school principals, early childhood educators, or children counselors should be more paying attention to these issues.